Isolation and Molecular Characterization of MethicillinResistant Staphylococcus pseudintermedius in dogs - Tamilarasu, S; Jayalaskhmi, V; Srinivasan, VM Vivek; Barbuddhe, SB; Antony, PX; Mukhopadhyaya, HK (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Isolation and Molecular Characterization of Methicillin-Resistant Staphylococcus pseudintermedius (MRSP) in dogs were carried out.A total of 25 ear swabs were collected aseptically from both diseased (otitis externa) and apparently healthy dogs (for vaccination)presented to teaching Veterinary Clinical Complex, Rajiv Gandhi Institute of Veterinary Education and Research (RIVER), Puducherry.On analysis of 25 ear swab samples, a total of 14 (56%) Staphylococcus pseudintermedius (S. pseudintermedius) isolates were recovered,6 (24%) isolates from healthy, and 8 (32%) isolates from diseased dogs. Among the 14 S. pseudintermedius isolates, eight isolates formecA, which is 21.40% (3/14), and 35.70% (5/14) of MRSP isolates were detected in healthy and diseased dogs, respectively. The presentstudy highlighted the presence of MRSP in dogs in Puducherry region.
Keywords: Dogs; Methicillin-resistance; mecA gene; Public health; Staphylococcus pseudintermedius